Exploring the Intellectual Structure of Islamic Education in Distance Learning with Bibliometric Analysis - Judijanto, Loso; Halim, Chandra (Eastasouth Institute, 2024)
This study explores the intellectual structure of Islamic education within the context of distance learning through a comprehensive bibliometric analysis. By mapping key themes, influential authors, and research trends, this research provides a detailed overview of the scholarly discourse and identifies emerging patterns and challenges. The thematic clusters identified include strategic approaches to digital pedagogy, the integration of multimedia resources, and the adaptation of traditional Islamic educational institutions to modern technologies. The analysis highlights significant research trends towards digital transformation and modernization while emphasizing the need to balance these with traditional educational values. Additionally, the study identifies opportunities for future research in developing culturally appropriate digital content and overcoming barriers such as the digital divide. The network of author collaborations reveals a segmented landscape with potential for increased inter-group cooperation. Overall, this research offers valuable insights into the evolving field of Islamic education and distance learning, guiding future studies and practical applications.n.